A Scoping Review of Human Teratogens and Their Impact on the Developing Brain: A Contribution From the ConcePTION Project - Bluett‐Duncan, M.; Adams, J.; Berkovitch, M.; Berlin, M.; Cahoon, A.; Clayton‐Smith, J.; Jackson, C.; Khanom, S.; Mølgaard‐Nielsen, D.; Richardson, J. L.; Simms, V.; Stellfeld, M.; et al. (Birth defects research, 2025)
ABSTRACT Certain medications, when used during pregnancy, are known to impact human prenatal development. Historically, little attention has been given to the impact of in utero exposure on the developing brain, despite the significance of known teratogen‐induced neurodevelopmental difficulties. This scoping review systematically identified and extracted neurodevelopmental outcome data for medications with established physical teratogenic effects and synthesized the key study characteristics. Medications with evidence of physical teratogenicity (n = 24) were defined by a panel of experts. Eligible studies reporting any neurodevelopmental outcomes following pregnancy exposure to the defined list of human structural teratogens were identified through electronic searches of MEDLINE and EMBASE. We identified 207 studies (254 publications) for inclusion, comprising 81 empirical cohorts and 126 case series. Concerningly, only 13 of 24 (54%) confirmed structural teratogens have been subject to any empirical investigation of neurodevelopmental outcomes. The mean time between authorization of known structural teratogens and the first empirical study investigating neurodevelopmental outcomes using a comparison group and formal data analysis is 33 years (Range: 11–64 years). When neurodevelopmental outcomes are investigated for medication exposures with physical teratogenic signatures, there are high levels of neurodevelopmental alterations (77%). These findings do not speak to a pharmacovigilance system that is functioning efficiently to identify and ameliorate neurodevelopmental risk, even for the medications with identified structural teratogenic risk. Given the high proportion of known physical teratogens exhibiting additional altered neurodevelopmental outcomes and the substantial lifetime burden of such alterations, to the individual and society, the timelines remain too long.